Testosterone deficiency and quality of life in Australasian testicular cancer survivors: a prospective cohort study. Issue 8 (August 2014) - O'Carrigan, B.; Fournier, M.; Olver, I. N.; Stockler, M. R.; Whitford, H.; Toner, G. C.; Thomson, D. B.; Davis, I. D.; Hanning, F.; Singhal, N.; Underhill, C.; Clingan, P.; et al.
Abstract This is the first prospective study in a contemporary Australian/New Zealand population to determine the prevalence of testosterone deficiency in testicular cancer survivors at 12 months from treatment, and any association with poorer quality of life. Hormone assays from 54 evaluable patients in a prospective cohort study revealed biochemical hypogonadism in 18 patients (33%) and low‐normal testosterone in 13 patients (24%). We found no association between testosterone levels and quality of life (all P > 0.05). Hypogonadal patients should be considered for testosterone replacement to prevent long‐term morbidity.